1991
DOI: 10.1111/j.1432-2277.1991.tb01989.x
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes toward organ donation: A survey in a Turkish community

Abstract: Abstract. A survey of public attitudes toward organ donation and transplantation was conducted in a Turkish community. The 1030 subjects were chosen using a random, stratified method. Some 50.5% of those interviewed were willing to donate their organs while 33.7% refused and 15.8% were uncertain. A total of 53.6% said they would consent to donate a deceased relative's organs. Reasons for refusal to donate organs were as follows: fear that their body would be cut into pieces (43.8%), religious beliefs (26.2%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 5 publications
2
16
0
2
Order By: Relevance
“…Individuals with more formal education were more likely to donate than were those with less formal education (Li, 2011). A survey in a Turkish community showed that females, the less educated and older people showed less willingness to donate organs (Bilgel et al, 1991). The same finding was concluded by Barcellos et al that higher education levels and a younger age were associated with a higher tendency to pledge (Barcellos et al, 2005).…”
Section: Discussionsupporting
confidence: 72%
“…Individuals with more formal education were more likely to donate than were those with less formal education (Li, 2011). A survey in a Turkish community showed that females, the less educated and older people showed less willingness to donate organs (Bilgel et al, 1991). The same finding was concluded by Barcellos et al that higher education levels and a younger age were associated with a higher tendency to pledge (Barcellos et al, 2005).…”
Section: Discussionsupporting
confidence: 72%
“…From our study in 1990, we found that religious misconceptions and false beliefs were significant components of negative public attitudes towards organ donation [3]. In the meantime, much has changed in terms of organ donation in Turkey.…”
Section: Introductionmentioning
confidence: 89%
“…A total of 594 particideath, however, the term "after death" was used in aliquestions. The questionnaires were filled out in the course of face-to-face interviews by the authors (Table 1) pants (60.4%) were aware of organ donatiin (2) No (1) TV (2) Newspapers, magazines, books (3) Health personnel (4) Friends and relatives ( 5 ) Other (specify) (I) Yes (3) I don't know (1) I do not want to be cut to pieces (2) Because of my religious beliefs (3) I will need my organs in my second life (4) No reason ( 5 ) Other (please specify) ( 2 ) Kidney (3) Liver (4) Pancreas (5) Skin (6) Bone ( 7 ) Heart (8) Lung (9) Whole body (10) Don't know (1) Yes (3) Don't know (1) I don't want him or her to be cut to pieces (2) Because of my religious beliefs (3) He or she will need his organs in his/her second life (4) Don't know ( 5 ) Other (please specify) (1) Yes ( transplantation was found to be strongly related to educational level (P < 0.0001); socio-economic status (P < 0.0001) age (P < 0.0001) and sex (P < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…This puzzling paradox is particularly notable among Muslims (29Y32). Survey research in the United Kingdom (29,33,34), Malaysia (35), Saudi Arabia (36), and Turkey (37,38) demonstrates that identifying with Islam is associated with negative attitudes toward organ donation and transplantation. Although these findings represent an international perspective, no studies, of which we are aware, have specifically examined the relationships between Islamic religiosity and attitude toward organ donation among American Muslims.…”
mentioning
confidence: 98%